2021
DOI: 10.1109/jphot.2021.3102229
|View full text |Cite
|
Sign up to set email alerts
|

Global Source Optimisation Based on Adaptive Nonlinear Particle Swarm Optimisation Algorithm for Inverse Lithography

Abstract: Source optimisation (SO) is an approved approach to improve the imaging quality in inverse lithography techniques. It is critical to apply an optimisation approach with high convergence efficiency and minimum errors in pixel-based SO. To improve the convergence efficiency of the pixel-based SO, a route of particle swarm optimiser (PSO) combined with the adaptive nonlinear control strategy (ANCS) is proposed in this study. As a global optimisation algorithm, ANCS-PSO has the attributes of breaking away from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Zhang Zhinan [19] et al increased the optimization rate of EUV SMO using SL-PSO (social learning PSO), in which the particles are updated based on historical information. Sun Haifeng [20] et al combined PSO with the adaptive nonlinear control strategy (ANCS) to break away from the local optimum.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang Zhinan [19] et al increased the optimization rate of EUV SMO using SL-PSO (social learning PSO), in which the particles are updated based on historical information. Sun Haifeng [20] et al combined PSO with the adaptive nonlinear control strategy (ANCS) to break away from the local optimum.…”
Section: Introductionmentioning
confidence: 99%
“…With this method, the target pattern, mask pattern, and wafer pattern are represented by level set functions, then the inverse lithography problem is regarded as a shape and topology optimization problem [32,33]. There are many other miscellaneous methods in inverse lithography, such as the genetic algorithm [11], the route of particle swarm optimizer combined with the adaptive nonlinear control strategy [35], deep convolution neural network methods [40,41]. A fuller review of inverse lithography techniques could be found in [25].…”
Section: Introductionmentioning
confidence: 99%